DESIGN AND DEVELOPMENT OF STREET CULINARY PHOTOBOOK IN SEKUPANG DISTRICT, BATAM - Hendi Sama; Maria Ulfa (CoMBInES - Conference on Management, Business, Innovation, Education and Social Sciences, 2022)
Batam City is a city that is engaged in industry, therefore many tourists visit. The fast culinary business in Batam City is very developed, because with a strategic location and rich in marine products. Business in the culinary field in Batam City takes various forms, in terms of place and the creativity of the UMKM. So that business competition in the culinary field is increasing, one of which is Street Culinary in Sekupang District, Batam, which is a business engaged in the culinary field. Street Culinary sells a variety of regional cuisine, with a strategic location and affordable prices. This activity aims to increase market share and provide information to the public about Street Culinary in Sekupang District, Batam. The final result of this research is a Photobook to promote the Foodcourt culinary business in Sekupang District, Batam. This photobook design uses Adobe InDesign 2020 Software and uses the Multimedia Development Life Cycle method which consists of 6 stages, namely concept, design, collecting material, assembly, testing, distribution. Therefore, the design and development of the Street Culinary Photobook in Sekupang Batam District is used as a medium of information to introduce its culinary.